Fisheries as ecosystem services: A case study of the Cauvery river basin, India - Pownkumar, V.; Ananthan, P.S.; Ekka, A.; Qureshi, Neha W.; T, Velumani (Frontiers in Environmental Science, 2022)
Habitat alterations and fragmentation caused by anthropogenic modifications of the riverine landscape have affected fish biodiversity by reducing the number of fish species. Fish are a major element of the aquatic environment, and they play an important role in maintaining ecosystem resilience. However, an incomplete understanding of links between river ecosystem functions and processes with fisheries is one of the major reasons for the alarming rate of decline of fish species . Recognizing the ecosystem services generated by fish populations is essential and is one step toward comprehensive, ecosystem-based management of riverine fisheries. Therefore, this paper is motivated by the need to explore the dimensions of fisheries as an ecosystem service. The data was collected from primary field observations and checklist-based key informant interviews at the seventeen fishing sites selected across an 800 km river stretch of the river. In addition, two focused group discussions with fishers at two sampling sites were held to provide first-hand knowledge of ecosystem services generated by fisheries. At first, the role of fisheries in generating ecosystem services for riverine ecosystem functioning and human demands is outlined using the Millennium Ecosystem Assessment approach. Then, the findings of a survey carried out from the headwaters to the delta of the Cauvery river are presented detailing the fisheries provisioning services, livelihoods, and other ecosystem services. The findings showed that the provisioning and cultural services are highly represented among the four categories of ecosystem services identified by the Millennium Ecosystem Assessment. However, in the literature reviewed, supporting, and regulating services are not well-represented. Based on these findings, the applicability of the ecosystem service concept can be elaborated to inform researchers and policymakers to enhance conservation efforts for fisheries.